SOFC or SOEC with long-life sealed interface and preparation method thereof
By adopting the sealing layer and spinel oxide coating of SiO2-MgO-Al2O3-SrO-V2O5 system, the problem of stress and cracks in the sealing interface of SOFC/SOEC stack in high temperature cycle is solved, and the long life of the stack is achieved Sealed interface improves overall performance and durability.
Patent Information
- Application Number
- CN202411398806.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The sealing interface of the SOFC/SOEC stack is prone to stress and cracks during high temperature cycles, resulting in seal failure and insufficient chemical stability of the sealing layer material, affecting the long life of the stack.
The sealing layer of SiO2-MgO-Al2O3-SrO-V2O5 system is adopted, and the metal connector is coated with spinel oxide coating. The metal connector is formed by phased heat treatment to form a high-density and strong adhesion coating to improve the metal connector. durability.
It significantly improves the durability and overall performance of the sealing interface, ensures the stable operation of the stack at high temperatures, extends the life of the stack, and avoids stress and damage caused by mismatch in the thermal expansion coefficient.
Smart Images

Figure CN118919797B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, and in particular to a SOFC or SOEC with a long-life sealing interface and a preparation method thereof. Background Art
[0002] Solid oxide fuel cells (SOFC) and solid oxide electrolyzers (SOEC) are widely used in distributed power generation, mobile power supplies, and transportation due to their high energy conversion efficiency and low pollution emissions. The cell, sealing layer, and metal interconnect are in contact with each other and together form a sealing interface. The sealing interface is the key part to ensure the normal operation of the SOFC / SOEC stack at high temperatures. In particular, the sealing interface composed of the sealing layer and the metal interconnect coating needs to have excellent thermal stability and chemical compatibility to ensure the operational stability and long life of the battery. However, at present, the sealing interface of the SOFC / SOEC stack has the following problems that affect the life of the stack: (1) The thermal expansion coefficients of the sealing layer, metal interconnect, and cell of the SOFC / SOEC stack are significantly different, which is easy to generate stress and cracks during high-temperature cycles, resulting in sealing failure; (2) The chemical stability of the sealing layer material at high temperatures is insufficient, and it is easy to react adversely with the electrolyte or electrode material, reducing the overall performance of the stack; (3) The hardness, mechanical strength, and fracture toughness of the sealing layer are relatively low, resulting in poor durability of the sealing layer, and it is easy to crack and rupture under hot and cold cycles and mechanical stress. Based on this, the present invention proposes a SOFC or SOEC with a long-life sealing interface and a preparation method thereof. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a SOFC or SOEC with a long-life sealing interface and a preparation method thereof.
[0004] The technical solution adopted by the present invention is:
[0005] One of the objects of the present invention is to provide a method for preparing a SOFC or SOEC having a long-life sealing interface, comprising the steps of:
[0006] S1. Determine the structure, geometric dimensions and constituent materials of each layer of the SOFC or SOEC stack, and prepare SOFC or SOEC cells;
[0007] S2, selecting a metal connector substrate and a coating material, preparing a metal connector and coating the surface of the metal connector with a protective coating;
[0008] S3. According to the material composition and ratio of the sealing layer, a sealing layer of the SiO2-MgO-Al2O3-SrO-V2O5 system is prepared;
[0009] S4, stacking and assembling a plurality of single battery units consisting of a sealing layer, a battery sheet, and a metal connector to obtain a SOFC or SOEC stack, and then pressurizing and heating the stack to complete interface sealing to obtain a SOFC or SOEC stack with a long-life sealing interface;
[0010] S5. Perform a continuous operation test and a hot and cold cycle test on the SOFC or SOEC stack prepared in step S4 to evaluate the stability and reliability of the stack under continuous operation and hot and cold cycles.
[0011] Furthermore, in step S2, the metal connector substrate is 430 stainless steel or Crofer 22 APU, and the coating material is spinel oxide coating.
[0012] Furthermore, the spinel oxide coating is at least one of nickel-iron spinel, cobalt-iron spinel and manganese-iron spinel.
[0013] Furthermore, the sealing layer in step S2 is made of the following components in molar mass percentage: SiO2 40-50%, MgO 20-30%, Al2O3 5-15%, SrO 5-15%, V2O5 5-12%, with a total content of 100%.
[0014] Furthermore, the sealing layer in step S3 includes the following components in molar mass percentage: SiO2 45-50%, MgO 25-30%, Al2O3 10-15%, SrO 8-12%, V2O5 8-10%, and the total content is 100%.
[0015] Furthermore, in step S3, the leakage rate of the sealing layer at the operating temperature of SOFC or SOEC is less than 0.04 sccm·cm -1 .
[0016] Furthermore, in step S3, the difference in thermal expansion coefficient between the sealing layer and the battery cell and the metal connector is ≤30%;
[0017] The resistivity of the sealing layer in step S3 at the operating temperature of SOFC or SOEC is ≥10×10 11 Ω·m;
[0018] The glass transition temperature of the sealing layer in step S3 is lower than the operating temperature of SOFC or SOEC, and the temperature difference is within 30%.
[0019] The softening temperature of the sealing layer in step S3 is higher than the operating temperature of the SOFC or SOEC;
[0020] In the step S3, the crystallization temperature of the sealing layer is higher than the softening temperature of the sealing layer.
[0021] Furthermore, the step S5 is specifically as follows:
[0022] S51, carrying out a hot and cold cycle test and a continuous operation test on the SOFC or SOEC stack prepared in step S5, monitoring the curves of temperature, voltage and current changing with the operation time during the hot and cold cycle and the continuous operation, and detecting the open circuit voltage, polarization curve and electrochemical impedance spectrum of the SOFC or SOEC stack once every hot cycle or 100 hours of continuous operation;
[0023] S52, according to the data recorded in step S51, determine the end life of the stack, firstly, determine the number of cold and hot cycle services or continuous operation time corresponding to the voltage decay to the end-of-life threshold at the rated working current density through polarization curve and electrochemical impedance spectrum data as its life; secondly, calculate the leakage rate during the service process according to the open circuit voltage of the SOFC or SOEC stack, and evaluate whether its leakage rate meets the requirement of <0.04 sccm·cm at the working temperature during each detection. -1 If it meets the requirements, the test will continue; if it does not meet the requirements, the number of cold and hot cycle service times or continuous operation time of the SOFC or SOEC stack at this time will be recorded as its life, and the minimum value will be selected as its terminal life;
[0024] S53, judging whether the number of hot and cold cycle service times and the continuous operation time recorded in step S52 meet the set requirements. If so, it means that the stability and reliability evaluation of the SOFC or SOEC stack under continuous operation and hot and cold cycles is qualified; if not, it means that the stability and reliability evaluation of the SOFC or SOEC stack under continuous operation and hot and cold cycles is unqualified.
[0025] Furthermore, the method further comprises the steps of:
[0026] According to the materials of the battery cells, metal connectors and sealing layers determined in steps S1, S2 and S3, a multi-physical field calculation model of the SOFC or SOEC stack based on the sealing interface is established, the temperature and stress distribution patterns of the components inside the stack are analyzed, and the number of hot and cold cycles when the maximum creep damage of the sealing layer reaches 0.99 or the maximum creep damage of the sealing layer when the set number of hot and cold cycles is obtained, and whether the sealing performance of the sealing interface meets the set requirements is evaluated. If so, proceed to steps S4 and S5. If not, return to step S3 to adjust the material ratio of the sealing layer.
[0027] A second object of the present invention is to provide a SOFC or SOEC having a long-life sealing interface.
[0028] The beneficial effects of the present invention are:
[0029] (1) The present invention provides a SOFC or SOEC with a long-life sealing interface and a preparation method thereof, wherein spinel is used as a coating material for a metal connector, and a high-density and highly adhesive spinel coating is formed by a staged heat treatment. The excellent oxidation resistance, chemical stability and electrical conductivity of the spinel coating significantly improve the durability and overall performance of the metal connector. The sealing layer material system is SiO2-MgO-Al2O3-SrO-V2O5. By adding an appropriate amount of V2O5 and controlling the ratio of SrO to V2O5, not only the resistivity of the sealing layer can be improved, but also the hardness and fracture strength of the sealing layer can be improved, thereby improving the durability of the sealing interface. In addition, by controlling the ratio of V2O5, the thermal expansion coefficient and airtightness of the sealing layer are adjusted to ensure that the sealing layer will not leak during service penetration and cause damage to the battery stack. In addition, the thermal expansion coefficient of the sealing layer is matched with the thermal expansion coefficient of the metal connector and the battery cell, thereby avoiding stress and damage caused by mismatched thermal expansion coefficients.
[0030] (2) The present invention provides a SOFC or SOEC with a long-life sealing interface and a preparation method thereof, wherein the sealing layer material system is SiO2-MgO-Al2O3-SrO-V2O5, and the crystallization temperature and peak crystallization temperature of the sealing layer prepared from the system are both greater than the operating temperature of the fuel cell stack, thereby avoiding excessive crystallization at the operating temperature, thereby maintaining its stability and mechanical strength; the softening temperature of the sealing layer is higher than the operating temperature of the SOFC, thereby ensuring that the sealing layer will not flow or deform at the operating temperature, thereby maintaining its structural stability and airtightness; in addition, the glass transition temperature of the sealing layer is slightly lower than or close to the operating temperature of the SOFC, thereby enabling the sealing layer to better adapt to deformation caused by thermal expansion differences, thereby maintaining good airtightness and providing a good sealing environment for the fuel cell stack. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 A schematic diagram of the partial structure of a SOFC single-layer stack prepared in Example 1 of the present invention;
[0033] Figure 2 The open circuit voltage variation curve of the SOFC stack prepared in Example 1 of the present invention during the thermal cycle;
[0034] Figure 3The microstructure of the sealing interface of the SOFC stack with an A10 sealing layer prepared in Example 1 of the present invention after 30 hot and cold cycles;
[0035] Figure 4 The microstructure of the sealing interface of the SOFC stack with an A0 sealing layer prepared in Example 1 of the present invention after 5 hot and cold cycles;
[0036] Figure 5 The microstructure of the sealing interface of the SOFC stack with the A15 sealing layer prepared in Example 1 of the present invention after 10 hot and cold cycles;
[0037] Figure 6 A multi-physics field calculation model of a SOFC stack established in Example 2 of the present invention;
[0038] Figure 7 This is a stress distribution diagram of the sealing layer of the SOFC stack with an A10 sealing layer prepared in Example 2 of the present invention;
[0039] Figure 8 This is a stress distribution diagram of the sealing layer of the SOFC stack with an A0 sealing layer prepared in Example 2 of the present invention;
[0040] Fig. 9 This is a stress distribution diagram of the sealing layer of the SOFC stack with an A5 sealing layer prepared in Example 2 of the present invention.
[0041] Labels in the figure: 1. cathode layer; 2. barrier layer; 3. electrolyte layer; 4. anode functional layer; 5. anode support layer; 6. sealing layer; 7. metal connector; 8. battery cell. DETAILED DESCRIPTION
[0042] The present invention provides a SOFC or SOEC with a long-life sealing interface and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0043] The present invention is described in detail below with reference to the accompanying drawings.
[0044] Example 1
[0045] This embodiment provides a solid oxide fuel cell with a long-life sealing interface, and the preparation process thereof is as follows.
[0046] S1. Prepare a cell sheet according to the structure of a single cell of SOFC and the constituent materials of each layer structure.
[0047] Specifically, the structure and materials of the battery cell of this embodiment are shown in Table 1 below.
[0048] Table 1 Cell structure and materials
[0049]
[0050] S2. Select a metal connector substrate and a coating material, and apply a protective coating on the surface of the metal connector.
[0051] Specifically, in this embodiment, the metal connector substrate is Crofer 22 APU with a thickness of 4000 μm, and the coating material is nickel-iron spinel. The steps of coating the protective coating on the surface of the metal connector are as follows:
[0052] (1) Surface treatment of the metal connector substrate may be performed by mechanical polishing, pickling, or plasma cleaning to remove oxides and impurities on the surface of the metal connector substrate;
[0053] (2) Preparation of nickel nitrate and ferric nitrate The nickel nitrate solution and the ferric nitrate solution are mixed and stirred evenly, and the solution is treated by a sol-gel process. The pH value of the mixed solution is adjusted to 9.0-11.0 by adding ammonia or ethanolamine to promote gelation of the solution. The mixed solution is allowed to stand or heated until a gel is formed. The formed gel is dried at 80-100°C to remove moisture, and then the dried gel powder is calcined at 600-800°C to form a spinel structure. Coating materials;
[0054] (3) The spinel structure The coating material powder is dispersed in a spray solvent to form a suspension, and the suspension is evenly sprayed on the surface of the metal connector substrate using a spray gun, and the coating thickness is controlled between 10 and 50 microns, specifically 30 microns in this embodiment, to ensure the mechanical strength and electrochemical properties of the coating;
[0055] (4) The metal interconnect substrate coated with the spinel coating is subjected to a staged heat treatment to form a dense spinel oxide coating, specifically:
[0056] The first stage of heat treatment (pre-sintering): carried out in a protective atmosphere (such as nitrogen or inert gas), the heat treatment temperature is set to 600℃~800℃, the heating rate is 1~3℃ / min, and the heat treatment time is 1~3h to preliminarily solidify the coating and form a spinel phase;
[0057] The second stage heat treatment (post-sintering): carried out in static air, the heat treatment temperature is set to 1000℃~1200℃, the heating rate is 1~3℃ / min, and the heat treatment time is 2~4h to form a dense spinel oxide layer and optimize the structure of the spinel phase;
[0058] Cooling: After heat treatment, slowly cool to room temperature to reduce thermal stress and maintain the integrity of the coating.
[0059] Specifically in this embodiment, in a heat treatment furnace in a nitrogen atmosphere, the metal connector substrate coated with the spinel coating is heated from room temperature to 700°C at a heating rate of 2°C / min, and is kept at this temperature for 120 minutes; after the insulation is completed, the nitrogen gas is stopped, and the substrate is continued to be heated from 700°C to 1100°C at a heating rate of 2°C / min, and is kept at this temperature for 180 minutes; finally, the metal connector substrate coated with the spinel coating is cooled to room temperature by natural cooling.
[0060] S3. Prepare a sealing layer of SiO2-MgO-Al2O3-SrO-V2O5 system according to the material components and proportions of the sealing layer.
[0061] Specifically, in this embodiment, in order to study the performance of sealing layers with different component ratios, 7 groups of sealing layers were prepared. The material components and ratios of the 7 groups of sealing layers are shown in Table 2 below.
[0062] Table 2 Material composition and ratio of sealing layer
[0063]
[0064] According to the material components and proportions of the sealing layer, the sealing layer is prepared by the following preparation method, specifically:
[0065] (1) First, the raw materials SiO2, MgO, Al2O3, SrO, and V2O5 are uniformly mixed according to the molar mass ratio in Table 2 above, and the total amount is 100 mol%;
[0066] (2) After the raw materials are mixed evenly, they are melted at 1300-1400° C. for 1-2 hours. Specifically, in this embodiment, they are melted at 1400° C. for 2 hours to obtain a glass frit. After rapid cooling, the glass frit is crushed, ground or ball-milled, and sieved to obtain a glass powder with a particle size of ≤30-45 μm.
[0067] (3) glass powder is mixed with solvent, binder, plasticizer, dispersant and defoamer in a mass ratio of 2.5-3.5:1:1:1:1:1 to form a glass sealing raw material. In this embodiment, 3:1:1:1:1:1 is used. Then, the glass sealing raw material is ball-milled for 12-24 hours by a planetary ball mill until it is evenly dispersed to obtain a stable sealing layer slurry with good fluidity and moderate viscosity. The above solvent is deionized water, and ethanol (such as 99% ethanol) can also be used; the binder is polyvinyl alcohol (PVA), and polymethyl cellulose (PMMA) can also be used; the plasticizer is phthalate, and polyvinyl alcohol ether can also be used; the dispersant polyvinyl alcohol (PVA) can also be a polyether (such as Triton X-100); the defoamer is a silicon-based defoamer;
[0068] (4) After vacuum degassing, the sealing layer slurry is poured into a slurry tank, and a casting blank with uniform thickness is formed by a casting machine. After drying for 24 hours, a casting sheet with a thickness of about 0.4 mm is obtained, and then naturally dried;
[0069] (5) Placing the dried sealing layer cast sheet on a cutting device and cutting it into corresponding shapes and sizes according to the requirements of the SOFC / SOEC stack;
[0070] (6) The cut sealing layer is sintered, firstly, the temperature is increased from room temperature to 200°C at a heating rate of 1~3°C / min, and kept at this temperature for 30 minutes; then, the temperature is increased from 200°C to 450°C at a heating rate of 1~3°C / min, and kept at this temperature for 30 minutes; then, the temperature is increased from 450°C to 800~1000°C at a heating rate of 0.5~2°C / min, and kept at this temperature for 180 minutes; after the sintering is completed, the temperature is cooled to room temperature at a cooling rate of 0.5~2°C / min. Specifically, in this embodiment, the temperature is first increased from room temperature to 200°C at a heating rate of 2°C / min, and kept at this temperature for 30 minutes; then, the temperature is increased from 200°C to 450°C at a heating rate of 2°C / min, and kept at this temperature for 30 minutes; then, the temperature is increased from 450°C to 850°C at a heating rate of 1°C / min, and kept at this temperature for 180 minutes; after the sintering is completed, the temperature is cooled to room temperature at a cooling rate of 1°C / min.
[0071] The performance tests and evaluations of the sealing layer samples prepared above were mainly conducted on differential thermal analysis, thermal expansion coefficient, resistivity and Vickers hardness tests to obtain the glass transition temperature (Tg), softening temperature (Tf), crystallization temperature (Tc), peak crystallization temperature (Tp), Vickers hardness and fracture toughness of the sealing layer, as well as the thermal expansion coefficient and resistivity at a working temperature of 750°C. In addition, the thermal expansion coefficient of the battery cell and the metal connector was also tested.
[0072] Specifically, the above test processes are as follows:
[0073] (a) Thermal expansion coefficient test
[0074] During the thermal expansion coefficient (CTE) test, the sample is placed in a thermomechanical analyzer (TMA) or a differential thermal expansion instrument (Dilatometer). After the equipment is calibrated for length and temperature, a temperature program is set from room temperature to the highest temperature, and an appropriate atmosphere (such as air, nitrogen or argon) is selected. The expansion measurement is performed in air at a heating rate of 5 °C / min, and the curve of the sample length changing with temperature is recorded to calculate the thermal expansion coefficient. The CTE value is determined based on the slope of the expansion curve in the temperature range of 25~800 °C.
[0075] (b) Differential thermal analysis test
[0076] The glass transition temperature (Tg), softening temperature (Tf), crystallization temperature (Tc) and peak crystallization temperature (Tp) of the glass sealing layer were determined using a comprehensive thermal analyzer system. The test temperature was 0~1200℃, the heating rate was 15℃ / min, and the test gas atmosphere was air.
[0077] The glass transition temperature (Tg) is the temperature at which the glass material changes from the glass state to the rubber state; the softening temperature (Tf) is the temperature at which the material begins to soften and lose its rigidity, and is an important indicator of the material's transition from a solid state to a flowable state; the crystallization temperature (Tc) is the temperature at which the glass material begins to precipitate a crystalline phase during the cooling process; the peak crystallization temperature (Tp) is the temperature at which the crystal phase generation rate of the glass or glass ceramic material reaches its maximum value during the heating or cooling process.
[0078] (c) Resistivity test
[0079] The resistivity of glass at different temperatures was measured using a Zahner electrochemical workstation and a standard four-probe method. The test conditions were a 2 V voltage applied in air and a temperature range of 25-800 °C.
[0080] (d) Vickers hardness and fracture toughness test
[0081] The Vickers hardness of the sealing layer samples was measured using a microhardness tester with a diamond indenter. A load of 10 N was applied to the polished sample and the holding time was 15 s. Ten measurements were performed on each sample and the average value was taken.
[0082] Vickers hardness and fracture toughness can be calculated by measuring the indentation size and the crack tip extension length, the formula is as follows:
[0083] ;
[0084] ;
[0085] in, is the Vickers hardness (GPa); is the applied load (N); and are the diagonal length of the indentation (m); is the fracture toughness (MPa·m 1 / 2 ); is the Vickers indenter constant, equal to 0.016; is the elastic modulus (GPa); is the average radial crack length (m) measured from the center of the indentation.
[0086] (e) Air tightness test
[0087] The air tightness of the sealing material is characterized by the leakage rate, which is defined as the leakage flow rate through the sealing material per unit length, in units of sccm·cm -1 The sealing performance test device consists of a temperature control system, a pressurization system and a measuring gas circuit system. The temperature control system includes a muffle furnace, a K-type thermocouple and a programmable temperature controller. The pressurization system adopts a pneumatic hydraulic system. The measuring gas circuit system includes an air source, a pressure reducing valve, a pneumatic set valve, a diaphragm pressure gauge, a flow meter, a sealing chamber and a connecting hose. A sealing layer sample with uniform thickness is selected and cut into a U-shaped sample with an outer length of 110mm×110mm and an inner length of 100mm×100mm. The U-shaped sealing layer sample is fixed between two steel plates to form a sealing chamber. The volume of the sealed inner gas storage tank is 200 cm 3 , high temperature glue is applied to the joint surface of the sealing layer sample and the steel plate to ensure close fit, the heating rate is 1℃ / min, the test gas is air, the external load is 0.25MPa, and the ventilation pressure is 10.3kPa. During the test, the gas enters the sealing chamber through the measuring gas path, and stops entering when the air pressure in the sealing chamber reaches the set value. Only when the air pressure decays after the gas leaks, the airflow enters the sealing chamber. The leakage is reflected by the flow meter reading, and the leakage rate can be calculated by measuring the time it takes for the air pressure to drop to 2.1 kPa.
[0088] The formula for calculating the leakage rate is:
[0089] ;
[0090] in, , are the gas pressures at the end and start of the test, respectively. , The time when the test ends and the time when the test starts, respectively. is the outer circumference of the sealing layer sample to be tested, is the volume of the gas tank.
[0091] The performance test results of the above-mentioned anode support layer, metal connector and sealing layer are shown in Table 3 below.
[0092] Table 3 Performance test results of anode support layer, metal connector and sealing layer
[0093]
[0094] Among the above parameters such as thermal expansion coefficient, glass transition temperature (Tg), softening temperature Tf (℃), crystallization temperature (Tc), peak crystallization temperature (Tp), Vickers hardness, fracture toughness, resistivity and leakage rate, firstly, the thermal expansion performance matching between the sealing material and the battery cell and metal connector and the airtightness of the sealing material are the most critical parameters. The thermal expansion matching between the sealing material and the battery cell and metal connector is crucial to avoid stress and damage in high temperature working environment. It is necessary to ensure that the difference in thermal expansion coefficient between the sealing layer and the anode support layer and the metal connector is ≤30% to avoid stress and damage caused by thermal expansion mismatch; airtightness directly determines whether leakage will occur during service and cause damage to the battery stack. The airtightness of the sealing material is characterized by the leakage rate, and its leakage rate must meet <0.04 sccm·cm at working temperature. -1 ; Secondly, resistivity is also a very important parameter. Low resistivity helps reduce power loss and improve battery efficiency. However, in order to ensure the insulation performance of the sealing material, the resistivity must be ≥10×10 11 Ω·m; Third, Vickers hardness and fracture toughness are important parameters to ensure the durability of the stack. Higher hardness helps to improve the durability of the material, but it is necessary to balance the relationship between hardness and sealing. Higher fracture toughness can prevent cracks and ruptures under thermal cycles and mechanical stress; In addition, the glass transition temperature (Tg), softening temperature (Tf), crystallization temperature (Tc) and peak crystallization temperature (Tp) of the sealing material must be matched and coordinated with the operating temperature of the SOFC / SOEC stack to maintain the integrity of the seal, which is essential for maintaining the long-term mechanical stability, airtightness and durability of the SOFC system during high-temperature operation and hot and cold cycles. Among them, a glass transition temperature (Tg) slightly lower than or close to the operating temperature of the SOFC / SOEC stack ensures that the material maintains sufficient elasticity to adapt to thermal expansion without excessive softening. On the contrary, a glass transition temperature (Tg) higher than the operating temperature may cause the sealing interface to become brittle and stress to increase, thereby posing a risk of failure. A softening temperature (Tf) higher than the operating temperature of the SOFC / SOEC stack is essential to prevent material flow, but the softening temperature (Tf) Too close to the operating temperature or too low can cause deformation and leakage. Finally, the crystallization temperature (Tc) and peak crystallization temperature (Tp) must exceed the SOFC / SOEC stack operating temperature to avoid unnecessary crystallization.
[0095] Through comprehensive analysis of the test results in Table 3, it can be seen that the comprehensive performance of the sealing layer sample A10 is the best.
[0096] S4, stacking and assembling the sealing layer, the battery cell, and the metal connector, and then pressurizing and heating them to complete the interface sealing, so as to obtain a single-layer SOFC stack with a long-life sealing interface, such as Figure 1 shown.
[0097] Specifically, the steps are:
[0098] S41, placing the sealing layer cast sheet prepared in step S3 on a cutting device, and cutting it into a first and second circular sealing layer according to the assembly requirements of the SOFC stack;
[0099] S42, placing the anode-side metal connector on the SOFC stack assembly platform, placing a first circular sealing layer in the PEN groove in the middle of the metal connector, and placing a second circular sealing layer around the metal connector, with a width of 10 cm;
[0100] S43. Apply glass glue to the remaining exposed parts of the metal connector to prevent the adjacent metal connectors from directly contacting each other and causing a short circuit.
[0101] S44, placing the battery cell on the upper part of the sealing layer 1, with the anode support layer of the battery cell facing downward and the cathode side facing upward; placing the same sealing layer 1 on the upper part of the cathode side of the battery cell, and placing the cathode side metal connector on the upper part of the round-shaped sealing layer 2, ensuring that the gap between the two metal connectors can accommodate the battery cell, and keeping the upper and lower surfaces of the battery cell in close contact with the metal connector;
[0102] S45. Place the stacked SOFC stack into a sintering furnace, apply a pressure of 0.14 MPa to the SOFC stack using a cylinder and a pressure rod, and then use the sintering furnace to heat and sinter the SOFC / SOEC stack to ensure that the sealing layer is bonded to the battery cells and metal connectors to complete the interface sealing. The above sintering process is the same as the above step S3.
[0103] S5. Evaluate the stability and reliability of the single-layer SOFC stack prepared in step S4 under continuous operation and hot and cold cycles. The specific steps are as follows:
[0104] S51, conducting a hot and cold cycle test and a continuous operation test on the SOFC stack prepared in step S4, monitoring the curves of temperature, voltage and current changing with the operation time during the hot and cold cycle and the continuous operation, and detecting the open circuit voltage, polarization curve and electrochemical impedance spectrum of the SOFC stack once every hot cycle or 100 hours of continuous operation;
[0105] S52. Determine the end life of the stack according to the data recorded in step S51. First, determine the number of cold and hot cycle services or continuous operation time corresponding to the voltage decaying to the end-of-life threshold at the rated working current density through polarization curve and electrochemical impedance spectrum data as its life. The end-of-life threshold is usually set to 20% of the voltage at the initial moment. Second, calculate the leakage rate during the service process according to the open circuit voltage of the SOFC stack, and evaluate whether its leakage rate meets the requirement of <0.04 sccm·cm at the working temperature during each detection. -1 If it meets the requirements, the test will continue; if it does not meet the requirements, the number of cold and hot cycle service times or continuous operation time of the SOFC stack at this time will be recorded as its life, and the minimum value will be selected as its terminal life;
[0106] Specifically, the process of calculating the leakage rate during service using the open circuit voltage OCV is:
[0107] The relationship between the open circuit voltage and gas partial pressure of the SOFC / SOEC stack satisfies the Nernst equation:
[0108] ;
[0109] in, is the open circuit voltage of SOFC, is the standard electrode potential, is the universal gas constant, R = 8.314 J / (mol·K); is the absolute temperature (K), is the Faraday constant (96485 C / mol); is the number of electrons (for oxygen reduction / oxidation reactions, is 4); and are the oxygen partial pressures at the cathode and anode respectively. If air is introduced into the cathode, the oxygen partial pressure at the cathode side is the oxygen partial pressure in the air, 0.21 atm;
[0110] Gas leakage will cause the partial pressure of the anode and cathode gases to change, thus affecting the OCV. Assuming that oxygen leaks from the cathode to the anode, the leakage increases the partial pressure of oxygen at the anode, thereby reducing the OCV. By measuring the difference between the actual OCV and the theoretical OCV, the leakage rate can be evaluated. Theoretically, the OCV without leakage is:
[0111] ;
[0112] in, is the anode oxygen partial pressure in the absence of leakage;
[0113] Due to the presence of leakage, the actual measured OCV is:
[0114] ;
[0115] in, is the anode oxygen partial pressure in case of leakage;
[0116] Based on the difference between the actual OCV and the theoretical OCV, the oxygen partial pressure of the leak can be calculated. The anode oxygen partial pressure in the case of leakage is:
[0117] ;
[0118] The leakage rate calculation formula is:
[0119] ;
[0120] in, is the anode side volume, is the time of measurement;
[0121] S53, judging whether the number of hot and cold cycle service times and the continuous operation time recorded in step S52 meet the set requirements. If so, it means that the stability and reliability evaluation of the SOFC stack under continuous operation and hot and cold cycles are qualified; if not, it means that the stability and reliability evaluation of the SOFC stack under continuous operation and hot and cold cycles are unqualified.
[0122] Specifically in this embodiment, the sealing layer samples of A10, A0, A5, and A15 are selected to prepare the corresponding single-layer SOFC stacks. Taking the hot and cold cycle test as an example, it is generally required that the hot and cold cycle life of the SOFC stack during commercial operation is at least 20 times. The working conditions of the hot and cold cycle test are: working temperature 750°C, anode fuel gas 0.5 L / min / piece, fuel utilization rate 65.02%, specifically: in the hot and cold cycle test, the SOFC stack is installed in an electric heating furnace and gradually heated to the reduction temperature and working temperature. When the temperature is raised to the working temperature of 750°C, the performance of the SOFC stack is evaluated. The electrochemical performance of the SOFC stack is measured using a fuel cell test system equipped with a temperature, electrical load, and gas flow controller. The power density of the battery is obtained according to the current-voltage (IV) curve at the working temperature; in addition, after the SOFC / SOEC stack is raised from room temperature to 750°C and the reduction process is completed, a DC electronic load (IT8814B, ITECH) is used to measure the SOFC / SOEC stack from 0mA / cm 2 To 450 mA / cm 2 Polarization curve under current density. Gamry Reference 3000AE electrochemical workstation is used to monitor the EIS of the battery in the open circuit state, with a frequency range of 10 mHz ~100 kHz. After the test is completed, the stack is at 300 mA / cm 2The output voltage was evaluated for stability at 0.5 °C·min. -1 The temperature was cooled to room temperature at a rate of 100 °C to complete a cycle, and the open circuit voltage, polarization curve and electrochemical impedance spectrum of the SOFC stack were tested every time after a thermal cycle. In the last thermal cycle, when the electric heating furnace was cooled to 150 °C, the power supply and hydrogen supply were turned off, and the tooling was dismantled when the temperature dropped to room temperature.
[0123] The test results show that the number of hot and cold cycle service and voltage decay rate of the single-layer SOFC stacks prepared by the sealing layer samples of A10, A0, A5 and A15 are shown in Table 4. The life criterion of the four single-layer stacks is "300 mA / cm 2 The voltage under the load of current density decays to 20% of the initial voltage.
[0124] Table 4 Hot and cold cycle service times and voltage decay rate of single-layer SOFC stack
[0125]
[0126] Note: The open circuit voltage is an important parameter for evaluating SOFC performance. It is usually equal to the theoretical potential of the battery unless there is electrolyte leakage. When the actual open circuit voltage is lower than the theoretical open circuit voltage, it indicates that there may be a seal leak. However, when there is only a small leak, the stack can still work normally, but the leakage rate reaches 0.04 sccm·cm -1 When the battery stack fails, it cannot work properly.
[0127] like Figure 2 As shown in the figure, as the thermal cycle proceeds, the open circuit voltage of the four groups of SOFCs shows a gradually decreasing change pattern. The voltage attenuation rate of the SOFC stack prepared with the A10 sealing layer at the open circuit voltage after 30 thermal cycles is 2.6711%, the voltage attenuation rate of the SOFC stack prepared with the A0 sealing layer at the open circuit voltage after 5 thermal cycles is 13.9749%, the voltage attenuation rate of the SOFC stack prepared with the A5 sealing layer at the open circuit voltage after 10 thermal cycles is 5.8528%, and the voltage attenuation rate of the SOFC stack prepared with the A15 sealing layer at the open circuit voltage after 7 thermal cycles is 15.1464%. The voltage attenuation rates of the average open circuit voltage of the SOFC stacks prepared with the A10, A0, A5, and A15 sealing layers are 0.0921% / time, 3.4937% / time, 0.6503% / time, and 3.7866% / time, respectively.
[0128] After testing, it was found that when the A10 sample was used as the sealing layer, the number of hot and cold cycle service times met the requirements, while when A0, A5, and A15 were used as the sealing layer, the number of hot and cold cycle service times did not meet the requirements.
[0129] In addition, the microstructure of the sealing interface of the single-layer SOFC stack prepared by the A10 sealing layer after 30 cold and hot cycles was detected, such as Figure 3 As shown; the microstructure of the sealing interface of the single-layer SOFC stack prepared by the A0 sealing layer was detected after 5 hot and cold cycles, as shown Figure 4 As shown; the microstructure of the sealing interface of the single-layer SOFC stack prepared by the A15 sealing layer was detected after 7 hot and cold cycles, as shown Figure 5 As shown. Figure 3 , Figure 4 , Figure 5 It can be seen that after the single-layer SOFC stack prepared with A10 sealing layer failed after 30 hot and cold cycles, its sealing interface only had tiny cracks at the contact interface between the sealing layer and the metal connector, while the single-layer SOFC stack prepared with A0 sealing layer had larger cracks at its sealing interface after 5 hot and cold cycles, especially severe cracking between the sealing layer and the metal connector; after the single-layer SOFC stack prepared with A15 sealing layer failed after 7 hot and cold cycles, its sealing interface had severe cracking, and the cracks penetrated the entire sealing layer, posing a risk of leakage.
[0130] Example 2
[0131] The difference between this embodiment 2 and embodiment 1 is that before performing step S4, this embodiment also establishes a multi-physical field calculation model of the SOFC or SOEC stack based on the sealing interface according to the materials of the battery cell, metal connector, and sealing layer determined in steps S1, S2, and S3, analyzes the distribution law of temperature and stress of each component inside the stack, as well as creep strain and creep damage, and evaluates whether the sealing performance of the sealing interface meets the set requirements. If the set requirements are met, steps S4 and S5 are performed. If not, the method returns to step S3 to adjust the material ratio of the sealing layer. Specifically:
[0132] (1) According to the structure of the SOFC stack, the COMSOL Multiphysics finite element software is used to establish a multi-physics calculation model of the SOFC stack that couples electrochemistry, heat transfer, flow and material transfer, such as Figure 6 As shown, the material parameters and geometric parameters of the SOFC stack and the sealing interface are set, the control equations for electrochemistry, heat transfer, flow and material transfer are set, and the boundary conditions and assumptions required for finite element simulation are set according to the actual working conditions;
[0133] (2) Perform finite element simulation calculations in COMSOL Multiphysics to obtain the temperature field distribution of the SOFC stack as a whole and the sealing layer;
[0134] (3) Based on the temperature field distribution obtained in step (2), a solid mechanics analysis is performed on the SOFC stack to obtain the stress field distribution of the SOFC stack as a whole and the sealing layer, and the number of hot and cold cycles when the maximum creep damage of the sealing layer reaches 0.99 or the maximum creep damage of the sealing layer when the set number of hot and cold cycles is reached;
[0135] (4) Analyze the stress field of the sealing layer and the maximum creep damage of the SOFC stack sealing layer to determine the stress distribution of the sealing layer and the influence of creep damage on the sealing performance. For the stress field of the sealing layer, the maximum stress should be ≤50MPa. For creep damage, the number of hot and cold cycles when the maximum creep damage of the sealing layer reaches 0.99 should be greater than the set number of hot and cold cycles (usually set to 20 times) or the maximum creep damage of the sealing layer when it reaches the set number of hot and cold cycles should be <0.99. If this condition is not met, it means that the sealing performance of the sealing interface does not meet the set requirements, and the material ratio of the sealing layer needs to be adjusted.
[0136] In this embodiment 2, the stress field distribution of the sealing layer obtained by simulating the above A0, A5, A10, and A15 is as follows: Figure 7 , 8 , as shown in 9, wherein, Figure 7 is the stress field distribution of A10 sealing layer, Figure 8 is the stress field distribution of A0 sealing layer, Fig. 9 The stress field distribution of the A5 sealing layer, the maximum compressive stress results of each sealing layer, and the number of hot and cold cycles when the maximum creep damage of the sealing layer is 0.99 are shown in Table 5.
[0137] Table 5 Maximum compressive stress of different sealing layers and the number of hot and cold cycles when the maximum creep damage of the sealing layer is 0.99
[0138]
[0139] It can be seen from Table 5 that during the operation of the SOFC stack, the sealing layer will inevitably be subjected to compressive stress. Although the maximum compressive stress of the A10, A0, A5, and A15 sealing layers is less than 50MPa, the difference is actually very large. Among them, the maximum compressive stress of the A10 sealing layer is the smallest, and the maximum compressive stress of the A0 sealing layer is the largest. This is because V2O5 is added to the A10 sealing layer, and by controlling the ratio of V2O5 to SrO, the thermal expansion coefficient of the sealing layer is small compared with the battery cell and the metal connector, thereby reducing the compressive stress caused by the mismatch of thermal expansion coefficients during the operation of the SOFC stack; in addition, within the operating range of the SOFC stack, the crystallization process of the sealing layer will form a crystalline phase, which will aggravate the mismatch of thermal expansion coefficients between the glass phase and the crystalline phase, thereby causing thermal stress concentration and cracks inside the sealing layer during the SOFC thermal cycle. After V2O5 is added to the A10 sealing layer, its crystallization temperature is significantly increased. , which reduces the precipitation of the crystalline phase of the sealing layer, and further reduces the stress concentration caused by the difference in thermal expansion coefficients between the glass phase and the crystalline phase of the sealing layer itself; in addition, too much V2O5 addition is not good, because when the amount of V2O5 is too much, it will lead to more crystal phase precipitation, which will increase the thermal expansion coefficient of the overall material, which may make the microstructure of the material rough, resulting in greater stress inside the material when the temperature changes, affecting its thermal stability; too much V2O5 addition will also lead to a decrease in the electrical conductivity and mechanical strength of the material, and excessive addition of V2O5 will increase the cost of the material.
[0140] Therefore, in practical applications, the amount of V2O5 added needs to be optimized through experiments to achieve the best performance balance.
[0141] In addition, during the operation of the SOFC stack, the crystallization process of the sealing layer will form a crystalline phase, which will gradually penetrate into the anode side and easily cause interface damage under stress or external load. As the number of thermal cycles increases, the precipitation of the crystalline phase leads to an increase in the number of holes and cracks in the sealing layer, and the cracks gradually expand under stress, especially the crystalline phase area is more susceptible to damage, which eventually leads to the fracture of the sealing layer. Due to the high crystallization temperature of the A10 sealing layer, it significantly reduces the precipitation of the crystalline phase, thereby reducing the generation of holes and cracks, and further improving the sealing performance of the sealing layer.
[0142] In addition, for the creep damage of the sealing layer, the number of hot and cold cycles when the maximum creep damage of the A10 and A5 sealing layers reaches 0.99 exceeds 20 times, but the number of hot and cold cycles of A10 can reach 56 times, which is significantly higher than A5, indicating that A10 has the best sealing performance.
[0143] It should be noted that some parts not described in the present invention can be implemented by adopting or drawing on existing technologies.
[0144] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a SOFC or SOEC having a long-life sealing interface, characterized in that: Includes steps: S1. Determine the structure, geometric dimensions and constituent materials of each layer of the SOFC or SOEC stack, and prepare SOFC or SOEC cells; S2. Selecting a metal connector substrate and a coating material, preparing a metal connector and coating a protective coating on the surface thereof, and subjecting the metal connector coated with the protective coating to a staged heat treatment; the coating material is a spinel oxide, and the spinel oxide is at least one of nickel-iron spinel, cobalt-iron spinel, and manganese-iron spinel; S3. According to the material components and proportions of the sealing layer, a sealing layer of the SiO2-MgO-Al2O3-SrO-V2O5 system is prepared; S4, stacking and assembling a plurality of single battery units consisting of a sealing layer, a battery sheet, and a metal connector to obtain a SOFC or SOEC stack, and then pressurizing and heating the stack to complete interface sealing to obtain a SOFC or SOEC stack with a long-life sealing interface; S5, performing a continuous operation test and a thermal cycle test on the SOFC or SOEC stack prepared in step S4 to evaluate the stability and reliability of the stack under continuous operation and thermal cycle; The sealing layer in step S3 includes the following components in molar mass percentage: SiO2 45-50%, MgO 25-30%, Al2O3 10-15%, SrO 8-12%, V2O5 8-10%, with a total content of 100%; In step S3, the difference in thermal expansion coefficient between the sealing layer and the battery cell and the metal connector is ≤30%; Also includes the steps: According to the materials of the cell, metal connector and sealing layer determined in steps S1, S2 and S3, a multi-physics field calculation model of the SOFC or SOEC stack based on the sealing interface is established, the distribution law of temperature and stress of each component inside the stack, as well as creep strain and creep damage are analyzed, and whether the sealing performance of the sealing interface meets the set requirements is evaluated. If the set requirements are met, steps S4 and S5 are performed. If not, the material ratio of the sealing layer is adjusted back to step S3, specifically: (1) According to the structure of the SOFC or SOEC stack, the COMSOL Multiphysics finite element software is used to establish a multi-physics calculation model of the SOFC or SOEC stack that couples electrochemistry, heat transfer, flow and material transfer, and set the material parameters and geometric parameters of the SOFC or SOEC stack and the sealing interface, set the control equations for electrochemistry, heat transfer, flow and material transfer, and set the boundary conditions and assumptions required for finite element simulation according to the actual working conditions; (2) Perform finite element simulation calculations in COMSOL Multiphysics to obtain the temperature field distribution of the entire SOFC or SOEC stack and the sealing layer; (3) Based on the temperature field distribution obtained in step (2), a solid mechanics analysis is performed on the SOFC stack to obtain the stress field distribution of the SOFC or SOEC stack as a whole and the sealing layer, and the number of hot and cold cycles when the maximum creep damage of the sealing layer reaches 0.99 or the maximum creep damage of the sealing layer when the set number of hot and cold cycles is reached; (4) Analyze the stress field of the sealing layer and the maximum creep damage of the sealing layer of the SOFC or SOEC stack to determine the stress distribution of the sealing layer and the influence of creep damage on the sealing performance. For the stress field of the sealing layer, the maximum stress should be ≤50MPa. For creep damage, the number of hot and cold cycles when the maximum creep damage of the sealing layer reaches 0.99 should be greater than the set number of hot and cold cycles, or the maximum creep damage of the sealing layer when it reaches the set number of hot and cold cycles should be <0.
99. If this condition is not met, it means that the sealing performance of the sealing interface does not meet the set requirements, and the material ratio of the sealing layer needs to be adjusted.
2. The method for preparing a SOFC or SOEC having a long-life sealing interface according to claim 1, characterized in that: In the step S2, the metal connector substrate is 430 stainless steel or Crofer 22 APU.
3. The method for preparing a SOFC or SOEC having a long-life sealing interface according to claim 1, characterized in that: The leakage rate of the sealing layer in step S3 at the operating temperature of SOFC or SOEC is less than 0.04 sccm·cm -1 .
4. The method for preparing a SOFC or SOEC having a long-life sealing interface according to claim 1, characterized in that: The resistivity of the sealing layer in step S3 at the operating temperature of SOFC or SOEC is ≥10×10 11 Ω·m; In step S3, the glass transition temperature of the sealing layer is lower than the operating temperature of the SOFC or SOEC, and the temperature difference is within 30%; The softening temperature of the sealing layer in step S3 is higher than the operating temperature of the SOFC or SOEC; In the step S3, the crystallization temperature of the sealing layer is higher than the softening temperature of the sealing layer.
5. The method for preparing a SOFC or SOEC having a long-life sealing interface according to claim 1, characterized in that: The step S5 is specifically as follows: S51, carrying out a hot and cold cycle test and a continuous operation test on the SOFC or SOEC stack prepared in step S4, monitoring the curves of temperature, voltage and current changing with the operation time during the hot and cold cycle and the continuous operation, and detecting the open circuit voltage, polarization curve and electrochemical impedance spectrum of the SOFC or SOEC stack once every hot cycle or 100 hours of continuous operation; S52, according to the data recorded in step S51, determine the end life of the stack, firstly, determine the number of cold and hot cycle services or continuous operation time corresponding to the voltage decay to the end-of-life threshold at the rated working current density through polarization curve and electrochemical impedance spectrum data as its life; secondly, calculate the leakage rate during the service process according to the open circuit voltage of the SOFC or SOEC stack, and evaluate whether its leakage rate meets the requirement of <0.04 sccm·cm at the working temperature during each detection. -1 If it meets the requirements, the test will continue; if it does not meet the requirements, the number of cold and hot cycle service times or continuous operation time of the SOFC or SOEC stack at this time will be recorded as its life, and the minimum value will be selected as its terminal life; S53, judging whether the number of hot and cold cycle service times and the continuous operation time recorded in step S52 meet the set requirements. If so, it means that the stability and reliability evaluation of the SOFC or SOEC stack under continuous operation and hot and cold cycles is qualified; if not, it means that the stability and reliability evaluation of the SOFC or SOEC stack under continuous operation and hot and cold cycles is unqualified.
6. A SOFC or SOEC having a long-life sealed interface, characterized in that: The method is prepared by any one of claims 1 to 5.
Citation Information
Patent Citations
Method for predicting creep life of solid oxide fuel cell stack
CN116879782A